Altas habilidades ou superdotação : políticas públicas e atendimento educacional em uma diretoria de ensino paulista - Mani, Eliane Morais de Jesus (Universidade Federal de São Carlos, 2015)
Students with high ability or giftedness are known as the audience of the Special Education, supported by the legal provisions, which guarantee adequate educational attention for the full development of their potential and talents in an inclusive perspective. The school system of the State of São Paulo, which configures the Brazil‟s largest one, in accordance with national guidelines, states by its own public policies the recognition of the needs for specialized pedagogical care when considering this segment of students. However, it is not uncommon the invisibility of this school population, by numerous factors, such as myths, lack of knowledge on the subject, lack of public policies on Special Education, among others. Such problem involves the lack of educational responses, showing that there is a significant gap regarding the provision of education quality to students with high ability or giftedness. In recent decades the scene of the Brazilian education has passing through many changes, regardless the educational management follows the same direction. Therefore, an inclusive education requires a democratic and participative management, which contribute to the promotion of educational practices and administrative actions, such as the implementation of specialized pedagogical care services to meet the educational needs of all diversity of students. Then, the goals of this research are: i) to analyze the knowledge of the management team of an executive board of the State of São Paulo about the concept, forms of identification and provision of specialized educational services for students with high ability or giftedness; ii) to describe the provision of special education services offered in educational public policy, in the perspective mentioned above. To this end, it has used an exploratory descriptive research with a case study. This study included 22 managers of Educational Board of a city located in the state of São Paulo using a questionnaire to understand the profile of these professionals and the conception of the work on the thematic of high abilities or giftedness students. The results showed significant progress with respect to the legal standards for educational transformation in an inclusive perspective. However, the effects of these documents do not reflect in an egalitarian context for students with high ability or giftedness in the studied school network, specifically within the Board of participant education, since the results revealed that the issue of knowledge multiplication in the schools is incipient. It is inferred, therefore, that it is one of the factors that impacts the lack of attention to this portion of students.
High abilities or giftedness : public policies and educational service at a paulista teaching departament
Keywords: Educação especial; Altas habilidades; Superdotação; Gestão escolar; Special education; High abilities or giftedness; School management; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO